Sport nutrition : from lab to kitchen - LinkJeukendrup, Asker (Meyer & Meyer Sport, 2010)
Sports Nutrition: From Lab to Kitchen is written by leaders in the field who discuss the latest science and translate the scientific findings into a practical message. This book bridges the gap between science and practice